2018
DOI: 10.15171/jnp.2018.35
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxic effects of low-dose zinc oxide nanoparticles in rats

Abstract: Background: The use of zinc oxide nanoparticles (ZNPs) in various products such as biosensors, sunscreens and nourishment added substances is increasing. Objectives: In the present work the impacts of ZNP on kidney of rats was explored. Materials and Methods: In this experimental study male Wistar rats were used. Trial groups received 5, 50 and 300 mg/kg ZNP (ZNP-1 to ZNP-3) for 2 weeks. Control group received only normal saline. blood urea nitrogen (BUN), creatinine (Cr) and uric acid were considered as bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
4
5
0
Order By: Relevance
“…Conversely, 60 mg ZONPs group highlighted degeneration of renal tissue including tubular disorganization and apoptotic cells, extravasated RBCS throughout tissue, and congestion in blood vasculature. This agreed with [121] who revealed that zinc oxide nanoparticles exerted a destructive effect on the kidney. Moreover, it was found that these nanoparticles had a toxic effect on the renal tissue at a high concentration.…”
Section: C-kidneysupporting
confidence: 91%
“…Conversely, 60 mg ZONPs group highlighted degeneration of renal tissue including tubular disorganization and apoptotic cells, extravasated RBCS throughout tissue, and congestion in blood vasculature. This agreed with [121] who revealed that zinc oxide nanoparticles exerted a destructive effect on the kidney. Moreover, it was found that these nanoparticles had a toxic effect on the renal tissue at a high concentration.…”
Section: C-kidneysupporting
confidence: 91%
“…Low dose caused more severe histopathological changes than a higher dose. Similar results were obtained on apoptotic index also [52]. Several workers agree that lower doses of NPs are more toxic than higher doses.…”
Section: In Vitro Studiessupporting
confidence: 84%
“…These results were in line with separate lead studies 46,47,48 that reported significant elevations in mean BLL and accumulation of significant amount of lead in thyroid gland more than control groups. It was assumed that the thyroid gland is a sensitive organ for lead accumulation in humans, 49 As well, these results are parallel to results of separate ZnO‐NPs studies 50,51,52 which demonstrated accumulation of ZnO‐NPs in various tissues of rodents as the liver, brain, kidney, and spleen. The oral NP form of ZnO dissolves in the stomach with release of zinc ions before absorption, 53 it is easier for NPs to penetrate the biological membranes and enter the bloodstream because of their smaller size 54…”
Section: Discussionmentioning
confidence: 71%